Future PM2.5 emissions from metal production to meet renewable energy demand. (1st April 2022) - Rathod, Sagar D; Bond, Tami C; Klimont, Zbigniew; Pierce, Jeffrey R; Mahowald, Natalie; Roy, Chaitri; Thompson, John; Scott, Ryan P; Hoal, Karin Olson; Rafaj, Peter
Abstract: A shift from fossil fuel to renewable energy is crucial in limiting global temperature increase to 2 °C above preindustrial levels. However, renewable energy technologies, solar photovoltaics, wind turbines, and electric vehicles are metal-intensive, and the mining and smelting processes to obtain the needed metals are emission-intensive. We estimate the future PM2.5 emissions from mining and smelting to meet the metal demand of renewable energy technologies in two climate pathways to be 0.3–0.6 Tg yr −1 in the 2020–2050 period, which are projected to contribute 10%–30% of total anthropogenic primary PM2.5 combustion emissions in many countries. The concentration of mineral reserves in a few regions means the impacts are also regionally concentrated. Rapid decarbonization could lead to a faster reduction of overall anthropogenic PM2.5 emissions but also could create more unevenness in the distributions of emissions relative to where demand occurs. Options to reduce metal-related PM2.5 emissions by over 90% exist and are well understood; introducing policy requiring their installation could avoid emission hotspots.